TEKNIK TOKEN EKONOMI TERHADAP KONSENTRASI ANAK HIPERAKTIF DI SEKOLAH LUAR BIASA - NUR KOMARIYAH, UTIK (Jurnal Pendidikan Khusus, 2017)
ABSTRACT:Concentration was focusing attention or thinking to something. By concentrating, all things could be recorded well in the brain memory and then they could easily be existed anytime needed. One of the difficulties which often happened to hyperactive children was concentration. If it was not solved soon the children would have experienced difficulty in developing their academic ability. This research purpose was to observe the concentration of hyperactive children. This research used Single Subject Research (SSR) kind with A-B design. The technique of data collection used was observation. The technique of data analysis used was visual analysis in condition and visual analysis among condition. Based on the result of visual analysis in condition, the baseline phase indicated the unstable condition while the intervention phase indicated stable change and in visual analysis among condition the baseline phase to intervention phase was decreasing to increasing or better which meant it indicated positive change tendency. So, it could be concluded that the technique of economic token influenced positive toward the concentration of hyperactive children.   Keywords: Concentration, Economic Token